Degree of Professional Commitment of Principals and Teachers of Palestinian Government Secondary Schools from a Teachers' and Principals' Viewpoint - Abdeen, Mohmmad (Jordan Journal of Educational Sciences, 2010)
This study examined how teachers in Palestinian government secondary schools view principals' professional commitment and how principals view teachers' professional commitment.It aimed to identify any differences in their views with regard to gender, years of experience, qualification level.A stratified random sample of 270 principals and 564 teachers from government secondary schools at Palestinian West Bank governorates was selected; a validated and reliable questionnaire was distributed to this sample.Results showed that the degree of professional commitment of principals as perceived by teachers was "high", while the degree of teachers' professional commitment as perceived by principals was "medium".Significant differences between principals' and teachers' views of each other's professional commitment were found.Meanwhile, no significant differences were found in teachers' views of principals' professional commitment due to gender, years of experience, and qualification level, nor in teachers' views of principals' commitment due to qualification level and years of experience, whereas significant differences were found in the latter's views due gender in favor of female teachers.